2009
DOI: 10.1093/nar/gkp309
|View full text |Cite
|
Sign up to set email alerts
|

PPISearch: a web server for searching homologous protein–protein interactions across multiple species

Abstract: As an increasing number of reliable protein–protein interactions (PPIs) become available and high-throughput experimental methods provide systematic identification of PPIs, there is a growing need for fast and accurate methods for discovering homologous PPIs of a newly determined PPI. PPISearch is a web server that rapidly identifies homologous PPIs (called PPI family) and infers transferability of interacting domains and functions of a query protein pair. This server first identifies two homologous families o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…To overcome these limitations, bioinformatics methods are expected to be useful for identifying PPIs in functional proteomics. Various computational methods have been proposed to predict PPIs, which include genomic context-based methods [13][14][15][16][17], structure-based methods [18][19][20][21], and sequence-based methods [22][23][24][25][26][27][28][29][30][31][32]. Genomic context-based methods such as gene-cluster and gene-neighbor methods are based on the search of pairs of genes that show a correlated position or behavior; these genes are assumed to encode proteins that interact with each other [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these limitations, bioinformatics methods are expected to be useful for identifying PPIs in functional proteomics. Various computational methods have been proposed to predict PPIs, which include genomic context-based methods [13][14][15][16][17], structure-based methods [18][19][20][21], and sequence-based methods [22][23][24][25][26][27][28][29][30][31][32]. Genomic context-based methods such as gene-cluster and gene-neighbor methods are based on the search of pairs of genes that show a correlated position or behavior; these genes are assumed to encode proteins that interact with each other [13].…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that sequence similarity above a certain threshold might be a reliable measure for identifying PPIs. Recently, several web servers, such as PPI-Search [30] and BIPS [31], have also been constructed for searching for homologous PPIs based on sequences. These services may assist in the identification of pairs of proteins that potentially interact.…”
Section: Introductionmentioning
confidence: 99%
“…This deductive inference has been applied to the identification of PPIs, on the assumption that homologous proteins share similar interaction patterns as well as similar functions [18]. A pair of interacting proteins in one species and their respective orthologs in another species, which are also known to interact with each other, have been traditionally defined as interaction-orthologs (interologs) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The consensus anchor, the subpocket–moiety interactions with statistical significance sharing by some particular protein kinases, can be regarded as a ‘hot spot’ that represents the conserved binding environments involved in inhibitor bindings and biological functions. As a result, a group of KIIs with consensus anchors can constitute a kinase-inhibitor family (KIF), which is analogous to a protein sequence family (18,19), a structure family (20) and a protein–protein interaction family (21). …”
Section: Introductionmentioning
confidence: 99%